2014
DOI: 10.1016/j.pnpbp.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of executive function related functional and anatomical alterations in aging brain

Abstract: Neurocognitive aging studies have focused on age-related changes in neural activity or neural structure but few studies have focused on relationships between the two. The present study quantitatively reviewed 24 studies of age-related changes in fMRI activation across a broad spectrum of executive function tasks using activation likelihood estimation (ALE) and 22 separate studies of age-related changes in gray matter using voxel-based morphometry (VBM). Conjunction analyses between functional and structural al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 81 publications
4
43
1
Order By: Relevance
“…It has been shown that there are great age-related gray matter reductions in the PFC (Raz et al, 2005; Fjell et al, 2009; Di et al, 2014), particularly in the inferior frontal subregions (Resnick et al, 2003). This atrophy may result in age-related memory deficits by affecting the use of self-initiated elaborative memory strategies in older adults (Craik and Rose, 2012; Kirchhoff et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there are great age-related gray matter reductions in the PFC (Raz et al, 2005; Fjell et al, 2009; Di et al, 2014), particularly in the inferior frontal subregions (Resnick et al, 2003). This atrophy may result in age-related memory deficits by affecting the use of self-initiated elaborative memory strategies in older adults (Craik and Rose, 2012; Kirchhoff et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many of the findings do not necessarily imply that hippocampal grey matter volume reduces with age, because the same relationship may be found in younger individuals. In fact, findings on age-related hippocampal shrinkage are partly heterogeneous as well: Although many studies revealed a negative relationship between hippocampal grey matter volume and age (e.g., [26, 27, 30, 38]), others did not [28]. …”
Section: Neurocognitive Changes Associated With Normal Agingmentioning
confidence: 99%
“…While a variety of age-related alterations in brain activation during cognitive control tasks have been reported, among the most common appears to be increased activation of the frontal cortex (DiGirolamo et al, 2001; Drag and Bieliauskas, 2010; Spreng et al, 2010; Gazes et al, 2012; Di et al, 2014). In particular, older adults are often found to show greater activation than younger adults in right frontal regions (reviewed in Dennis and Cabeza, 2008; Reuter-Lorenz and Park, 2010).…”
Section: Introductionmentioning
confidence: 99%